MBCL-15. TOXICITY PROFILE AND RESPONSE TO HIGH DOSE METHOTREXATE, BEVACIZUMAB, AND TEMOZOLOMIDE CHEMOTHERAPY REGIMEN IN CHILDREN WITH RECURRENT MALIGNANT PEDIATRIC BRAIN TUMORS: SINGLE INSTITUTION EXPERIENCE. Issue 2 (22nd June 2018) - Page, Margaret; Singh, Sumit; Ramini, Sasha; Kachurak, Kara; Edmondson, Jessica; Li, Rong; Waite, Emily; Bernstock, Joshua; Alva, Elizabeth; Reddy, Alyssa; Friedman, Gregory
Abstract: BACKGROUND: Standard, effective therapies for recurrent malignant pediatric brain tumors do not exist. High-dose methotrexate (HDMTX), bevacizumab, and temozolomide have been studied alone or with other agents, but a regimen combining these agents has not been described. We report the toxicity and tumor response for patients treated with this regimen. METHODS: We conducted a retrospective review of patients at Children's of Alabama with recurrent tumors treated with up to six 28-day cycles of HDMTX (8 grams/m 2 IV on day 2), bevacizumab (5-10 mg/kg IV on day 1, 14), and temozolomide (200 mg/m 2 po daily for 5 days after clearance of HDMTX). Response was measured by RANO criteria. Patients who responded to therapy received additional cycles of bevacizumab and temozolomide. RESULTS: Primary diagnoses included 5 medulloblastoma, 2 supratentorial PNETs, 1 choroid plexus carcinoma, and 1 ependymoma. Median age at diagnosis was 11 years (range 2-19). All patients received prior standard-of-care chemotherapy and/or radiation. Six had disseminated disease at recurrence. A total of 43 courses of therapy were administered (median 5.5 cycles/patient [range 2-6]). Toxicities included neutropenia (18.6%), thrombocytopenia (18.6%), hypertension (13.9%), skin rash (9.3%), and dysuria (7.0%). No hospitalizations for toxicity or leukoencephalopathy occurred. Four patients with medulloblastoma (80%) had a partial response with mean response time of 16 months (range 14-18). CONCLUSIONS: The combination of HDMTX, bevacizumab and temozolomide was well-tolerated in heavily pretreated children with recurrent malignant brain tumors. Partial responses lasting over a year were achieved in 80% of medulloblastoma patients. Further evaluation of this regimen is warranted.